Plantations for the tropics -- their role, extent and nature - Brown, A.G.; Nambiar, E.K.S.; Cossalter, C. (1997)
This chapter describes the context in which tropical forest plantations are expanding as a source of industrial wood and fuel. World demand for the former is increasing, but the rate of increase is slowing and is subject to fluctuations in economic activity. Dependency on fuelwood is very high in many countries, and it is not lessening overall. The use of planted trees by communities and industry to satisfy these demands is increasing. A small number of species have been very widely used, but there is merit in extending the choice available to growers, in part to better cater for the diverse biophysical and socioeconomic environments in tropical countries. The very varied climates and soils of the tropics are reflected in great variation in plantation yield, and there are many critical issues yet to be understood regarding sustainable production by tropical plantations. Several factors which cause low productivity are amenable to manipulation by managers. Experience from temperate regions can provide valuable guidance for both practice and research in the tropics. Wood requirements cannot be satisfied from native forests alone; plantations offer proven prospects for higher rates of production per unit area compared to native forests, and the production trend suggests that even forest-rich nations are shifting their reliance for wood supply from native forests to plantations. Long-term production with requisite environmental care is a challenge for both research and practice.